ANALISA SEBARAN KUALITAS AIR TANAH DI TPA PELAWI KABUPATEN OGAN KOMERING ULU SELATAN - meiwinda, eka rizki (Universitas Sulawesi Barat, 2023)
TPA Pelawi is 513 km from residential areas. TPA Pelawi implements an open dumping system. The purpose of this study was to determine the quality of the TPA groundwater and its distribution. Samples were taken as many as 4 stations, namely station 1 is river water, station 2,3, and 4 are groundwater samples. Based on the analysis of the data obtained, the quality of ground water in the Pelawi TPA is moderately polluted, Fe, Zn, Cd, Cr, Mn and Pb metals are found in the groundwater around the Pelawi TPA.